Melamine Foam with pH‐Responsive Wettability for Fast Oil Absorption and Desorption. Issue 10 (4th February 2022) - Ma, Junjun; Xie, Yangchun; Yang, Tao; He, Xiaohua
Abstract: Innovative 3D materials with the switchable wetting surface attract significant attention due to their application in oil/water separation. Herein, a fast pH‐responsive and highly effective melamine foam (MF) grafted with poly (2‐dimethylaminoethyl methacrylate) is prepared by surface‐initiated chain transfer radical polymerization. The as‐prepared MF displays superhydrophilic and superoleophobic surface in strong acid solution while it becomes superhydrophobic in neutral or basic solution. Therefore, it can be rapid to selectively absorb different types of oils from the oil–water mixture with a great absorption capacity of 54–117 g g −1  and automatically desorb oil in less than 60 s with a desorption efficiency of 99% (dichloromethane) in acid solution. Moreover, the as‐prepared MF possesses excellent recyclability, and the absorption capacity and the desorption efficiency are almost unchanged after 15 cycles. The pH‐sensitive MF with switchable wetting surfaces has great potential for the oily water separation. Abstract : The melamine foam (MF) modified by poly(2‐dimethylaminoethyl methacrylate) is successfully prepared by surface‐initiated chain transfer radical polymerization. The surface of the modified MF shows pH‐induced switchable wettability and the excellent oil absorption–desorption recyclability can be developed for applications in oil/water separation and oil recovery.